Genome-wide association studies and transcriptome analysis reveal novel genes associated with freezing tolerance in rapeseed (Brassica napus L.). - Guoqiang Zheng; Zigang Liu; Lixi Jiang; Qi Yang; Jiaping Wei; Zefeng Wu; Junmei Cui; Xiaoyun Dong; Xiaodong Cao; Xuezhen Yang; Ying Wang; Yongjie Gong; et al. (PLoS ONE)
Freezing stress is the main obstacle affecting the geographical distribution, growth, development, quality, and productivity of rapeseed (Brassica napus) in northern China. However, there is a little knowledge of rapeseed freezing tolerance mechanism. Here, 289 core germplasms collected from 36 countries were used to identify SNPs associated with freezing tolerance. We used RNA-seq data to narrow down the candidate genes identified by genome-wide association studies. The frequency distributions of phenotypic values and best linear unbiased estimates (BLUE) values for each trait conform to normal or approximately normal distributions, with good repeatability across various locations. The results showed that 594, 513, 7, and 45 SNPs were significantly associated with malondialdehyde, peroxidase, soluble protein, and relative electrolyte leakage, respectively. Based on these significantly associated SNPs, we identified 4,998 associated genes. Crossover analysis indicated that 73 genes were overlapped between GWAS and RNA-seq datasets, and 13 candidate genes involved in transmission and perception of freeze stress signals, lipid metabolism, reactive oxygen species (ROS) homeostasis, antifreeze proteins synthesis, and other metabolic processes. These results reveal novel genes associated with freezing tolerance in rapeseed, and provide a basis for further research and improvement of freezing tolerance in rapeseed.